Coxeter Functors for One Class of *-Quivers - Kruhlyak, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For one certain class of *-quivers, we construct Coxeter functors and describe their application to the description of families of orthoprojectors whose sum is a multiple of the identity operator.